Evaluating herbicide tolerance of industrial hemp (Cannabis sativa L.). Issue 1 (9th March 2020) - Flessner, Michael L.; Bryd, Jabari; Bamber, Kevin W.; Fike, John H.
Abstract: Industrial hemp ( Cannabis sativa L.) has a wide array of end uses which, when coupled with regulatory reductions in the United States, has spurred renewed interest in its production. Best management practices, including weed control, need to be evaluated. Since little is known about herbicide tolerance of hemp, studies were conducted to identify suitable options for grain or dual‐purpose (fiber and grain) production. Greenhouse experiments with pre‐emergence and postemergence herbicides were conducted to identify herbicide choices for subsequent field trials. In field studies, S ‐metolachlor was the safest pre‐emergence herbicide, resulting in 0 and ≤ 15% injury in 2017 and 2018, respectively, and a hemp stand count that was 97% of the nontreated check (pooled across years). All other pre‐emergence herbicides tested in the field resulted in ≥ 25% visible injury in at least one of the years and ≥ 24% stand reduction relative to the nontreated check (pooled across years). However, no grain yield differences were observed due to pre‐emergence herbicides relative to the nontreated check. Postemergence herbicides sethoxydim, quizalofop, bromoxynil, and clopyralid caused < 20% injury across rating timings and years and had similar grain yield as the nontreated check (588 kg ha −1 ). Our results indicate that S ‐metolachlor applied pre‐emergence or sethoxydim, quizalofop, bromoxynil, and clopyralid applied postemergence are suitable for hemp production, but some of these treatments caused transient visible injury. Future research should be conducted to corroborate results across cultivars, soil types (for pre‐emergence herbicides), and environments.